Experimental and theoretical study on ceiling temperature distributions in mountain tunnel with a lateral open shaft - Yuchun Zhang; Xinyu Liu; Rui Tan; Wei Hou; Longfei Chen; Shaoshuai Xing; Zhisheng Li; Yunhai Guo; Xiaoqing Han (Scientific Reports)
Abstract A series of fire experiments in a 1/10 scale model tunnel with a lateral open shaft were conducted. Analysis was performed to explore the maximum excess temperature and longitudinal temperature decay under the influence of a mechanical exhaust system with a lateral open shaft. Three different pool sizes and numerous extraction rates were considered. The experimental results yielded intriguing insights into the correlations between the rate of smoke extraction and the ceiling temperature. The variations in the temperature distribution of ceiling smoke upstream and downstream the fire source is different under the induced longitudinal velocity, especially for the near the fire source area. An analysis of the maximum excess temperature was conducted by inducing the heat loss coefficient $$δ$$ . It is 0.85 (0.71) for the induced dimensionless longitudinal velocity $${λ V_{s} }^{′} \le 0.19$$ $$\left( {\left( {λ V_{s} } \right){′}> 0.19} \right)$$ , which indicates the effect of a large velocity on the smoke heat loss. Then, a modified model of the maximum excess temperature was given for a tunnel utilizing lateral open shaft smoke extraction. In addition, a simple model was proposed to capture ceiling temperature decay, where the decay coefficients $$k_{i}$$ upstream and downstream of the fire source are proportional to $$1/Q^{^{′}1/3}$$ ( $$V_{in}{′} /Q^{^{′}1/3}$$ ) for $$( {λ V_{s} })^ {′} \le 0.19$$ $$\left( {\left( {λ V_{s} } \right){′}> 0.19} \right)$$ . The research results have certain guiding significance for the arrangement of fire protection, fire monitoring and early warning devices in mountain tunnels.